Depositional Environment and Source Rocks Potential of the Miocene Organic Rich Sediments, Balikpapan Formation, East Kutai Sub Basin, Kalimantan - Permana, ST.,M.Sc., Asep Kurnia; Sendjaja, Yoga Andriana; Panggabean, Hermes; Fauzely, Lili (Jurnal Geologi dan Sumberdaya Mineral, 2018)
The fluvial to deltaic sediments of the onshore petroleum prolific of the Mahakam Delta in the East Kutai Sub-basin constrain organic rich sediments particularly within the Balikpapan Formation. This formation has been recognized as a source rocks of the conventional oil and gas production in the Kutai Basin. However, the geochemical studies to understand the origin of organic matter and paleo-environmental condition of this formation are still limited. A 390 selected samples of organic rich sediments from the Balikpapan Formation were analyzed by using organic petrographic and geochemical analyses. These analyses were used to define the sedimentary organic matter and moreover the paleo-environment conditions during deposition and their implication to the source rocks and hydrocarbon potential. The organic rich shales and mudstones of this sediment have high total organic content (TOC) values in range of 0.05% – 15.63% and coals are ranging from 2.25% to 57.11%. They are and mainly dominated by vitrinite maceral, with minor liptinite and inertinite. The minerals mostly consist of clay minerals, with minor pyrite and oxide minerals (quartz and carbonates). Rock Eval Pyrolisis analysis results show low hydrogen index (HI) values (4 to 248.52mgHC/g TOC) and predominance of vitrinite maceral reveal prevalence of terrestrially derived type III organic matter and their potential to generate gas. The max temperature values which is ranging from 411 to 435°C and Ro ranges 0.7% - 0.64% implies a low to moderate thermal maturation levels for an active source rocks. The organic matter accumulation is mainly associated with black shales and coals in the delta plain environment, derived from terrigenous organic matter.Keyword: Depositional environment, source rocks, Balikpapan  Formation, Kutai Basin.